Effect of Culturally Adapted Dental Visual Aids on Oral Hygiene Status during Dental Visits in Children with Autism Spectrum Disorder: A Randomized Clinical Trial - Ala Aljubour; Medhat AbdElBaki; Omar El Meligy; Basma Al Jabri; Heba Sabbagh (MDPI AG, 2022)
Autism spectrum disorder (ASD) prevalence has escalated in the last few decades; it is common to have children with ASD seek dental treatment. Their unique behavior patterns prevent them from attending a regular dental setting and receiving proper oral hygiene instructions (OHI); therefore, culturally adapted dental visual aids are necessary to teach them proper OHI. The aim of this study was to assess the effectiveness of culturally adapted dental visual aids in improving oral hygiene (OH) status in children with ASD. A blinded, randomized, controlled clinical trial with sixty-four children with ASD were randomly divided into two groups according to the type of dental visual aids given to them. The experimental group received culturally adapted dental visual aids developed specifically for the study, and the control group received regular dental visual aids. OH status was assessed before and after using the dental visual aids, and data were processed using SPSS version 25.0. OH status improved significantly in both groups after using the dental visual aids (p < 0.001, p < 0.001), respectively. The experimental group showed significant improvement in comparison to the control group in OH status (p = 0.030). Both dental visual aids showed effectiveness in improving OH status in children with ASD.